Exploring the Linkage between Corruption and Economic Development in The Case of Selected Developing and Developed Nations - Audi, Marc; Ali, Amjad (International Journal of Economics and Financial Issues, 2019)
Corruption is like an epidemic that has the power to destroy a country’s socioeconomic, financial, human and political environment. It has severe consequences in developing countries. This study has examined the impact of existing human, political, financial and economic factors on corruption for a set of panel countries. The data from 1995 to 2004 is used to serve this purpose. For examining the stationarity of the variables, Levin- Lin-Chu (2002), Fisher-ADF and Fisher-PP tests are applied. Pedroni Residual based Co-integration and FMOLS by Phillips and Hansen (1990) test has been used for examining the co-integration among the variables of the model. The speed of adjustment and short-run relationship has been tested through VECM. The estimated results show that exports, GDP per capita and political stability have a negative impact on corruption, whereas imports, financial development, human development index, bureaucracy, democracy and the rule of law have a positive relationship with corruption. The simplified procedures of import and export will help reduce the practice of bribes and corruption. The governments should take steps not only to increase the income, but also to improve the people’s standard of living. There should be improvements in the political system. Democracy is also helpful to get rid of corruption. Keywords: Corruption, Economic Development, Financial Development, Human Development, Political Development, Ethics JEL Classifications: D7, O11, O15 DOI: https://doi.org/10.32479/ijefi.8052